Peningkatan Efisiensi Dokumentasi Melalui Perancangan Sistem Pengarsipan Surat Pada Kantor Kelurahan Sempaja Timur - Azelina Zahra Riadini; Sri Mar’ati Sholikhah; Lilis Sagita; Aurelia Novinta Taufik; Muhammad Hafizh Atthoriq; Asslia Johar Latipah (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
In this era of globalization, technological advancements have rapidly progressed, easing human tasks with the current technology that typically gets things done swiftly. Information technology in institutional settings serves as a means of knowledge and information management. Kelurahan Sempaja Timur is a local government office that serves the community in all matters related to governance. This office holds a plethora of data concerning incoming and outgoing correspondence. However, the archiving of these documents is still done manually, leading to a buildup of letters over time. Hence, there's a need for a system capable of handling the archiving of documents, facilitating both storage and swift, detailed retrieval when needed. This will expedite subsequent workflow processes.